Optimalisasi Penulisan Karya Tulis Ilmiah Mahasiswa dengan Aplikasi Mendeley dan Turnitin: Optimizing Student Scientific Writing Using Mendeley and Turnitin Applications - Cahyani, Dwi; Pranata, Widya Eka; Indrayani, A. Fahmi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The ability to produce scientific papers is one of the competencies that must be mastered by students in the academic world in higher education. Citation and plagiarism have a close relationship because, including reference sources through correct citation, it can prevent the author from committing plagiarism and show integrity in meeting ethical standards in writing scientific papers. Currently, many applications offer various features to facilitate students in managing references and avoiding plagiarism, including Mendeley and Turnitin. This community service activity is carried out in the form of training to provide real assistance to students to produce quality scientific papers through proper reference management and without being trapped in plagiarism. The training activities were divided into three sessions, the first session was the presentation of material by the resource person, in the second session each participant did the practice and the last session was the evaluation of the activity by giving practical assignments to determine the knowledge and skills of the training participants in using Mendeley and Turnitin in writing scientific papers. All students who participated as participants showed high interest and enthusiasm in participating in each session of the training activities. In addition, the results of the activity evaluation also showed an increase in the knowledge and ability of the trainees in making citations in scientific papers using Mendeley and checking the level of plagiarism of scientific papers using Turnitin.